Attention Map-Guided Visual Explanations for Deep Neural Networks - Junkang An; Inwhee Joe (Applied Sciences, 2022)
Deep neural network models perform well in a variety of domains, such as computer vision, recommender systems, natural language processing, and defect detection. In contrast, in areas such as healthcare, finance, and defense, deep neural network models, due to their lack of explainability, are not trusted by users. In this paper, we focus on attention-map-guided visual explanations for deep neural networks. We employ an attention mechanism to find the most important region of an input image. The Grad-CAM method is used to extract the feature map for deep neural networks, and then the attention mechanism is used to extract the high-level attention maps. The attention map, which highlights the important region in the image for the target class, can be seen as a visual explanation of a deep neural network. We evaluate our method using two common metrics: average drop and percentage increase. For a more effective experiment, we also propose a new metric to evaluate our method. The experiments were carried out to show that the proposed method works better than the state-of-the-art explainable artificial intelligence method. Our approach can provide a lower average drop and higher percent increase when compared to other methods and find a more explanatory region, especially in the first twenty percent region of the input image.